THE USE OF FRACTIONAL UNITS FOR APPROXIMATE CALCULATION METHOD OF POSITIONAL SPECIFICATIONS - Irina Lavrynenko; Sergey Viktorovich Lavrynenko; A. V. Lavrynenko; Nikolai Maltsev (Наука. Инновации. Технологии, 2022)
The paper proposes a new efficient method for determining the position characteristics of the system of residual classes through the use of the relative magnitude of num-bers and shows how its use for non-modular implementation of the major operations.